Associations Between Asthma Diagnosis/Asthma Exacerbation and Previous Proton-Pump Inhibitor use: A Nested Case-Control Study Using a National Health Screening Cohort - Choi, Hyo Geun; Min, Chanyang; Yoo, Dae Myoung; Tan, Bruce K.; Kim, Joo-Hee; Kim, Hwan Il; Park, Ji-Young; Park, Sunghoon; Hwang, Yong Il; Jang, Seung Hun; Jung, Ki-Suck (Frontiers in Pharmacology, 2022)
Background: Proton-pump inhibitors (PPIs) block acid secretion from gastric parietal cells; however, recent studies have reported that PPIs have antioxidant and anti-inflammatory properties in various cells. Newer PPIs are stronger inhibitors of acid secretion; however, the anti-inflammatory effects of these drugs have not been assessed. We evaluated anti-inflammatory effect of PPIs on the development of asthma/asthma exacerbation (AE) in a national health screening cohort. Methods: This case-control study comprised 64,809 participants with asthma who were 1:1 matched with controls from the Korean National Health Insurance Service-Health Screening Cohort. Conditional logistic regression analysis was used to evaluate the effect of previous PPI use on an asthma diagnosis in all participants. Unconditional logistic regression was used to assess the effect of PPI use on AE in participants with asthma. These relationships were estimated in a subgroup analysis according to PPI generation. Results: Overall, PPI use increased the risk of asthma diagnosis (adjusted odds ratio [aOR]=1.29, 95% confidence interval [CI]=1.23-1.35, P<0.001). Use of the first-generation PPIs was associated with asthma (aOR=1.34, 95% CI=1.18-1.52, P<0.001), while use of 2nd-generation PPIs was not (aOR= 0.97, 95% CI=0.82-1.15, P=0.748). In contrast, overall PPI use decreased the risk of AE in participants with asthma (aOR=0.79, 95% CI=0.75-0.84, P<0.001), although this effect was observed only for 2nd-generation PPIs (aOR=0.76, 95% CI=0.65-0.89, P=0.001). Conclusions: PPI use increased the risk for subsequent asthma diagnosis. However, this effect was confined to first-generation PPIs. Second-generation PPIs decreased the risk of AE.